Heart failure with reduced ejection fraction: predicting exercise intolerance with echocardiography. (14th October 2021) - Azul Freitas, A; Ferreira, C; Goncalves, V; Martinho, S; Almeida, J; Rosa, J; Campos, G; Jorge, E; Goncalves, L
Abstract: Introduction: Cardiopulmonary exercise testing (CPET) is routinely used in the prognostic evaluation of patients with heart failure with reduced ejection fraction (HFrEF). Left ventricular ejection fraction (LVEF) is a strong prognostic marker but have shown a bad correlation with exercise capacity. The aim of this study is to assess the relationship between echocardiographic parameters and exercise capacity in HFrEF patients. Methods: We retrospectively assessed all patients with HFrEF submitted to CPET and echocardiography between March and September of 2019. 73 patients were eligible for analysis. ANOVA test was used to compare Weber class groups regarding echocardiographic parameters. Multivariate linear regression with a stepwise approach was used to assess independent predictors of peak VO2 uptake. ROC curves were compared to assess the best parameter to discriminate a peak VO2 <10 ml/kg/min (Weber class D). Results: Mean age was 53.4±11.7 years with 72.6% being male. Mean LVEF was 29.2±7.7% and mean peak VO2 was 13.4±3.8 ml/kg/min. Between the Weber class groups, significant differences were found in left (LV) and right ventricular (RV) longitudinal strain (P<0.001 and P=0.005 respectively), in the left and right atrial reservoir strain (P=0.009 and P<0.001 respectively), in pulmonary velocity acceleration time (P=0.002) and in maximal tricuspid regurgitation velocity (TRmax) (P=0.014). Left ventricular ejection fraction, tricuspid annular plane systolic excursion, and ratio E/e' were not significantly different among exercise capacity groups. Additionally, only RV longitudinal strain (r2=0.225, P=0.008) and TRmax (r2=0.073, P=0.030) were independent predictors of peak VO2. RV longitudinal strain showed the best accuracy in discriminating a Weber class of D (AUC=0.731, 95% CI: 0.613–0.848, P=0.005) with a calculated cut of −8.6% and with a negative predictive value of 95%. Conclusion: RV longitudinal strain and TRmax seem to be the best echocardiographic predictors of exercise intolerance in patients with HFrEF. Since CPET is not widely available, these echocardiographic parameters can be clinically useful as a surrogate prognostic factor. Funding Acknowledgement: Type of funding sources: None.